2001
DOI: 10.1111/j.1365-2893.2001.00271.x
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of interferon randomized trials in the treatment of viral hepatitis C in naive patients: 1999 Update

Abstract: The aim of this study was to update our previous meta‐analysis of interferon (IFN) in the treatment of hepatitis C and to analyse new factors, namely, HCV RNA end‐point, patients with cirrhosis and patients with normal ALT. We use the Der Simonian and Laird method, with heterogeneity and sensitivity analyses. Seventy‐six randomized control trials (RCTs) in naive patients were found but we focused our analysis on 59 RCTs with chronic hepatitis C (26 vs. controls and 33 comparing different regimens) and on seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 84 publications
2
10
1
Order By: Relevance
“…Greater eradication of HCV infection by antiviral therapy has been documented in hemodialysis patients than in those with normal renal function (3,4,41,42,66,67), possibly reflecting the high antiviral drug plasma levels achieved because of reduced renal clearance. Actually, the clearance of PEG-IFN is reduced by 45% in patients with ESRD (68), being mainly affected by the permeability and pore size of dialyzers (69).…”
Section: Treatment Of Hcv Infectionmentioning
confidence: 99%
“…Greater eradication of HCV infection by antiviral therapy has been documented in hemodialysis patients than in those with normal renal function (3,4,41,42,66,67), possibly reflecting the high antiviral drug plasma levels achieved because of reduced renal clearance. Actually, the clearance of PEG-IFN is reduced by 45% in patients with ESRD (68), being mainly affected by the permeability and pore size of dialyzers (69).…”
Section: Treatment Of Hcv Infectionmentioning
confidence: 99%
“…[58,61,62] Some studies report that the risk of HCC is reduced in these patients independent of fibrosis stage, while among cirrhotic patients that achieve SVR incidence of HCC is reduced by 20%. [63][64][65] In the group of patients with chronic hepatitis treated with IFN ± ribavirin, the incidence rate of HCC is markedly reduced, while in the group of cirrhotic patients data are not sufficient to support the efficacy of therapy to preventing cancer. [64][65][66] A meta-analysis in 2010 compared 20 studies with 4,700 patients overall; the risk in treatment group of HCC was reduced (RR: 0.43, 95% CI: 0.33-0.56).…”
Section: Hcvmentioning
confidence: 99%
“…[63][64][65] In the group of patients with chronic hepatitis treated with IFN ± ribavirin, the incidence rate of HCC is markedly reduced, while in the group of cirrhotic patients data are not sufficient to support the efficacy of therapy to preventing cancer. [64][65][66] A meta-analysis in 2010 compared 20 studies with 4,700 patients overall; the risk in treatment group of HCC was reduced (RR: 0.43, 95% CI: 0.33-0.56). [58] Pinzoni et al [67] showed that the risk of developing HCC after achieving SVR persisted in patients with HCV-related cirrhosis: among 598 patients with CHC who underwent a complete course of treatment with Peg-IFN and ribavirin, 221 (37%) patients obtained a SVR and throughout the 10-year post-treatment follow-up, 5.8% of these 221 patients developed HCC.…”
Section: Hcvmentioning
confidence: 99%
“…Treatment with IFN alone is, however, generally associated with a sustained virologic response in fewer than 20% of patients [1][2][3]. Pegylated-interferon (PEG-IFN) given once a week with ribavirin (RBV) administered orally is more effective than a regimen of standard IFN given three times a week [4].…”
Section: Introductionmentioning
confidence: 99%